Advances in biomaterials for the treatment of retinoblastoma. (12th August 2022) - Farhat, Wissam; Yeung, Vincent; Ross, Amy; Kahale, Francesca; Boychev, Nikolay; Kuang, Liangju; Chen, Lin; Ciolino, Joseph B.
Abstract : An overview of the key developments in biomaterials as platforms for delivering chemotherapy for the management of retinoblastoma is provided in this review. Abstract : Retinoblastoma is the most common primary intraocular malignancy in children. Although traditional chemotherapy has shown some success in retinoblastoma management, there are several shortcomings to this approach, including inadequate pharmacokinetic parameters, multidrug resistance, low therapeutic efficiency, nonspecific targeting, and the need for adjuvant therapy, among others. The revolutionary developments in biomaterials for drug delivery have enabled breakthroughs in cancer management. Today, biomaterials are playing a crucial role in developing more efficacious retinoblastoma treatments. The key goal in the evolution of drug delivery biomaterials for retinoblastoma therapy is to resolve delivery-associated obstacles and lower nonlocal exposure while ameliorating certain adverse effects. In this review, we will first delve into the historical perspective of retinoblastoma with a focus on the classical treatments currently used in clinics to enhance patients' quality of life and survival rate. As we move along, we will discuss biomaterials for drug delivery applications. Various aspects of biomaterials for drug delivery will be dissected, including their features and recent advances. In accordance with the current advances in biomaterials, we will deliver a synopsis on the novel chemotherapeutic drug delivery strategies and evaluate these approaches to gain new insights into retinoblastoma treatment.